2021
DOI: 10.1111/anu.13409
|View full text |Cite
|
Sign up to set email alerts
|

Dietary lysine modulates growth performance, haemato‐biochemical indices, non‐specific immune response, intestinal enzymatic activities and antioxidant properties of rainbow trout, Oncorhynchus mykiss fingerlings

Abstract: The experimental trial was conducted to assess the appropriate utilization of dietary lysine (Lys) required for Oncorhynchus mykiss fingerlings. Six isonitrogenous (450 g/kg CP) and isoenergetic (20.90 kj/g GE) casein-gelatine based diets supplemented with varying concentrations of dietary Lys (14.0, 16.5, 19.0, 21.5, 24.0. and 26.5 g/kg, dry diet) were formulated. For each incremental level, all diets were randomly distributed in triplicate groups of 20 fish (1.79 ± 0.06 g/fish; 5.70 ± 0.42 cm/fish) and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 100 publications
(145 reference statements)
0
11
0
Order By: Relevance
“…Lysine is the most limiting amino acid in many plant proteins (Hauler & Carter, 2001; National Research Council (NRC) 2011). As an essential amino acid, lysine is significant for aquatic animals due to its role in growth, metabolism and immune response (Ahmed & Ahmad, 2021; Walton et al, 1984; Yang et al, 2020). Previous studies reported that appropriate lysine level improved the growth performance and feed utilization of grass carp ( Ctenopharyngodon idellus ; Dh et al, 2021), Nile tilapia ( Oreochromis niloticus ; Romaneli et al, 2021) and blunt snout bream ( Megalobrama amblycephala ; Cai et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lysine is the most limiting amino acid in many plant proteins (Hauler & Carter, 2001; National Research Council (NRC) 2011). As an essential amino acid, lysine is significant for aquatic animals due to its role in growth, metabolism and immune response (Ahmed & Ahmad, 2021; Walton et al, 1984; Yang et al, 2020). Previous studies reported that appropriate lysine level improved the growth performance and feed utilization of grass carp ( Ctenopharyngodon idellus ; Dh et al, 2021), Nile tilapia ( Oreochromis niloticus ; Romaneli et al, 2021) and blunt snout bream ( Megalobrama amblycephala ; Cai et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In sub‐adult grass carp, the activities of catalase (CAT) and glutathione peroxidase (GSH‐Px) increased with the increase of dietary lysine levels (Li et al, 2014). In rainbow trout ( Oncorhynchus mykiss ), an appropriate amount of lysine also increased the antioxidative status of fish (Ahmed & Ahmad, 2021). Nuclear factor erythroid 2‐related factor 2 (Nrf2) is a critical transcription factor in cellular oxidative stress response (Hui & Yang, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the intestinal trypsin and lipase activities were decreased by excessive dietary lysine, indicating the digestive function of H. wyckioides was adversely affected by the imbalance of dietary amino acids. Previous studies have also confirmed that an excessive lysine level might inhibit the activities of trypsin and lipase (Ahmed & Ahmad, 2021;Huang et al, 2022). Therefore, appropriate dietary lysine may enhance digestive enzyme activities and thereby improve the digestion and growth of fish (Li et al, 2014).…”
Section: Antioxidant-related Indexmentioning
confidence: 86%
“…Since LYS is a limiting EAA found in low quantities in vegetable proteins [27], it could be one of the main advantages of using eviscerated whole polychaetes as an additional ingredient in fsh-free aquafeeds. Furthermore, it has been documented that LYS above the minimum required dietary level is essential for the nonspecifc immune system of the rainbow trout, Oncorhynchus mykiss [28], and favors the gastrointestinal development of agastric fsh [29].…”
Section: Discussionmentioning
confidence: 99%